2016
DOI: 10.1051/e3sconf/20161201002
|View full text |Cite
|
Sign up to set email alerts
|

Full-waveform inversion of GPR data acquired between boreholes in Rustrel carbonates

Abstract: Abstract. Full waveform inversion (FWI) of seismic or Ground PenetratingRadar data provides high-resolution quantitative images of the constitutive parameters of the rock/soil which control seismic/GPR wave propagation. We developed a 2D inversion tool in the frequency domain adapted to the multi-parameter physics controlling GPR propagation in isotropic non dispersive media, i.e. dielectric permittivity and electrical conductivity. This inversion engine was previously tested using synthetic 2D data to mitigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…Based on several tests, we found that values of d a = 28 m and d b = 33 m were efficient, while in our case, the maximum sourcereceiver offset is slightly larger than 40 m. Figure 14(b) shows the isotropic solution without smoothing, while Fig. 14(c) displays an isotropic velocity model obtained from fullwaveform inversion (FWI) inversion using the same dataset by Pinard et al (2016). While tomography results are smoother, Figure 12 Distribution of the 6741 picked first-arrival traveltimes as a function of source-receiver elevations.…”
Section: A N I S Ot Ro P I C To M O G R a P H Y I N V E R S I O N On mentioning
confidence: 77%
See 4 more Smart Citations
“…Based on several tests, we found that values of d a = 28 m and d b = 33 m were efficient, while in our case, the maximum sourcereceiver offset is slightly larger than 40 m. Figure 14(b) shows the isotropic solution without smoothing, while Fig. 14(c) displays an isotropic velocity model obtained from fullwaveform inversion (FWI) inversion using the same dataset by Pinard et al (2016). While tomography results are smoother, Figure 12 Distribution of the 6741 picked first-arrival traveltimes as a function of source-receiver elevations.…”
Section: A N I S Ot Ro P I C To M O G R a P H Y I N V E R S I O N On mentioning
confidence: 77%
“…Our synthetic model has been constructed considering isotropic full‐waveform‐inversion results obtained from the same real crosshole ground‐penetrating radar (GPR) data as those used hereafter (Pinard et al ., 2016). We consequently designed a target model for vertical velocity vv (Fig.…”
Section: Evaluation Of the Tomographic Approach Using Synthetic Crossmentioning
confidence: 99%
See 3 more Smart Citations